Accessing medical equipment in developing countries through remanufacturing - Solomon Eze; Winifred Ijomah; Tse Chiu Wong (Journal of Remanufacturing, 2019)
While many developing countries may not afford state-of-the-art medical equipment, they may take advantage of the significant price reduction and other benefits of remanufacturing to solve their perennial healthcare problems that are aggravated by the shortage of medical equipment. As a first step towards implementing medical equipment remanufacturing in developing countries, the regulatory perspectives which plays a crucial role in the industry should be understood. However, since regulation of medical equipment is weak or inexistent in most developing countries, the regulatory perspectives with respect to remanufacturing or related activities in both the European Union (EU) and the United States of America (US) are first examined to determine their impacts. Unfortunately, there appears to be a lack of precise definition of remanufacturing for medical devices. An unambiguous definition is necessary to promote effective research, improve understanding, ensure uniformity of standards, drive quacks out of the remanufacturing market and thus, enhance customer confidence in remanufactured products. This paper proposes a definition for medical equipment remanufacture. The principal advantage of this definition is that it could be adopted in future research toward increasing access to functional medical equipment to developing countries through remanufacturing.
Keywords: 650; Medical device remanufacturing; Medical equipment remanufacturing; Medical devices for developing countries; Medical equipment for developing countries